2016 Glenn A. Fry Award Lecture: Mechanisms and Potential Treatments of Early Age-Related Macular Degeneration. Issue 10 (October 2017) - Fletcher, Erica Lucy
Abstract : ABSTRACT: Age-related macular degeneration (AMD) is the leading cause of irreversible vision loss in those older than 80 years. Understanding the mechanisms that cause this condition or its progression is critical for developing novel treatments. Here we summarize our studies evaluating the role of purine, adenosine triphosphate (ATP), in early AMD as well as photoreceptor loss and have also provided some insights to our investigations of a new laser treatment for those with early AMD. One of the receptors that are activated by ATP, P2X7, is expressed by neurons and immune cells and has a different function in each cell type. In neurons, P2X7 receptors form a ligand-gated ion channel, whereas on immune cells P2X7 receptors act as a scavenger receptor. These distinct functions have provided new insights to the mechanisms of AMD. On the one hand, high concentrations of ATP can cause photoreceptor death, most likely via stimulation of P2X7 receptors localized on photoreceptor terminals. On the other hand, P2X7 receptors mediate removal of dead and dying cells by monocytes. By understanding the fundamental cell biological changes that occur in patients and animal models of disease, we have uncovered mechanisms that may help us manage and treat patients in the future.